Peningkatan Produktivitas Anak Muda Indonesia Melalui Pelatihan Financial Life Skills (FLS) - Dewi, Vera Intanie; Detti, Regina; Iskandarsyah, Triyana; Barlian, Inge; Septina, Nina; Danil, Lilian (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2022)
Financial Life Skills (FLS) training is a participatory program and collaboration between USAID and the government of the Republic of Indonesia through the Youthwin Through Economic Participant Project (Yep Project). The Financial Life Skills training program also plays a role in contributing to financial literacy awareness for the community, especially the younger generation. The FLS training service method using the experiential learning cycle (ELC) training method. The trainer and participants will engage interactively through various activities such as simulations, role-plays, filling out worksheets, questions, and answer discussions. The ELC method is suitable for FLS training because participants' skills are not enough to hear and see, but participants can first experience training activities. At the end of the training, participants can experience changes in knowledge and attitude as provisions for changing behavior future. Based on the results of participant evaluation, this training provides benefits for the younger generation to become a generation that is productive and smart in managing finances to live prosperously in the future.